Hubungan Intensitas Penggunaan Internet Dengan Carpal Tunnel Syndrome - Reagen Jimmy Mandias; Hermi Meidelin Dengah (Fakultas Keperawatan, Universitas Klabat, 2019)
Abstract The intensity of excessive internet use through electronic media can increase the risk of carpal tunnel syndrome, which is a musculoskeletal disorder involving the human body system such as skeletal, nerve, and muscle. This relates to hand positions and repetitive movements such as tapping, swiping and scrolling. The purpose of this research is to analyze the relationship between the intensity of internet use with the symptoms of carpal tunnel syndrome in the students of the Faculty of Computer Science, University of Klabat. The research method uses descriptive correlation with cross sectional approach. 216 students from various levels have become respondents in this study, selected through purposive sampling. The results of this study found out that there was a positive and significant relationship between the intensity of internet use with symptoms of carpal tunnel syndrome with p = 0,000 (r = 0.33), where the higher the intensity of internet use the higher the symptoms of carpal tunnel syndrome. Based on the results of study researchers suggest that students can use the internet wisely for things that are useful, both in lecture activities and daily life. Keywords: Carpal tunnel syndrome, Intensity of internet use